Increasing Activities and Learning Outcomes of Human Excretion System through Matrix of Memory to Students of Class IXA MTsN 9 Hulu Sungai Tengah - Maslinawati Maslinawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
This research aimed to increase the activity of students of IXA class of MTSN 9 Hulu Sungai Tengah by applying the learning strategy of memory matrix, Increasing student learning result of class IXA MTSN 9 Hulu Sungai Tengah by applying learning strategy of memory matrix and Knowing teacher activity in class IXA MTSN 9 Hulu The Middle River on the human excretion system material that implements the memory matrix learning strategy. Setting this research is in class IXA MTsN 9 Hulu Sungai Tengah with number of student 33 people. With Research subjects are students and teachers. the success indicator of this research is the increasing ability of students understanding about the concept of Human excretion system with the standard of completeness of individual study 70 and 80% classically. The result of the class action research showed that the students' learning achievement of the IXA MTSN 9 Hulu Sungai Tengah class that applied the memory matrix learning strategy improved from 78.79% (cycle I) to 84.8% (cycle II). The activity of the IXA students of MTSN 9 Hulu Sungai Tengah class that applied the learning strategy of memory matrix increased at meeting 1 (66,7%) with good enough criterion, meeting 2 (75%) with good criteria, (100%) with very good criteria on meetings 3 and 4, and teacher activity in the IXA class MTSN 9 Hulu Sungai Tengah on the subject matter of human ecretion system through the learning strategy of memory matrix has increased, meeting 1 (75%) with good criterion, meeting 2 (83,3%) with criterion very good, to be (100%) with very good criteria at meetings 3 and 4.